Pendidikan Memoderasi Pengaruh Efektivitas Sistem Informasi Akuntansi, Kemampuan Pemakai, dan Motivasi Kerja Pada Kinerja Karyawan - Gumiyar, Kadek Geyong Aditya; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2022)
This study aims to determine the effect of education moderating the relationship between the effectiveness of accounting information systems, user capabilities, and work motivation on employee performance at the Lestari Bank Credit (BPR) Denpasar City. The population is all BPR Lestari in Denpasar City, totaling 14 units. The number of samples is 85 respondents who are management assessors of the performance of SIA users based on the saturation side method. The analysis technique used multiple linear regression analysis and MRA test. The results of the analysis show that the effectiveness of accounting information systems, user abilities, and work motivation have a positive effect on employee performance, education is not able to moderate the effect of accounting information system effectiveness and work motivation on employee performance, while education is able to moderate the influence of user abilities on employee performance at BPR Lestari in Denpasar City. Keywords:  Education; Accounting Information System Effectiveness; User Ability; Work Motivation; Employee Performance.